A small heat shock protein (SlHSP17.3) in tomato plays a positive role in salt stress - Cai, Guohua; Niu, Mingyu; Sun, Zhihao; Wang, Huakun; Zhang, Shuo; Liu, Fei; Wu, Yanqun; Wang, Guodong (Frontiers in Plant Science, 2024)
Small heat shock proteins (sHSPs) are molecular chaperones that are widely present in plants and play a vital role in the response of plants to various environmental stimuli. This study employed transgenic Arabidopsis to investigate the impact of the new tomato (Solanum lycopersicum) sHSP protein (SlHSP17.3) on salt stress tolerance. Transient conversion analysis of Arabidopsis protoplasts revealed that SlHSP17.3 localized to the cytoplasm. Furthermore, as suggested by expression analysis, salt stress stimulated SlHSP17.3 expression, suggesting that SlHSP17.3 is involved in the salt stress response of plants. SlHSP17.3-overexpressing plants presented greater germination rates, fresh weights, chlorophyll contents, and Fv/Fm ratios, as well as longer root lengths, lower reactive oxygen species (ROS) levels, and lighter cell membrane injury under salt stress. Furthermore, certain stress-related genes (AtCOR15, AtDREB1B, and AtHSFA2) were up-regulated in salt-stressed transgenic plants. Overall, SlHSP17.3 overexpression improved the salt stress resistance of transgenic plants, mainly through increasing AtCOR15, AtDREB1B, and AtHSFA2 expression.